Analisis Kepuasan Petani Terhadap Kinerja Penyuluh Pertanian Di Masa Pandemi Covid-19 (Studi Kasus di Desa Genteng Kecamatan Sukasari Kabupaten Sumedang) - Ning Srimenganti; Nataliningsih Nataliningsih; Erlangga Yosie Yunizar (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2022)
This This study aims to determine the performance of the instructor (tangibel) and (emphathy) in service to farmers during the pandemic Covid-19 and to determine the level of farmer satisfaction with the performance of the extension during the pandemic worker Covid-19 in Genteng Village, Sukasari District, Sumedang Regency. This research uses a case study method through a quantitative descriptive approach. The results of the IPA analysis show that the performance that is considered by farmers to have the highest interest is the ability of extension workers to use the local language, providing information about 3M policies (using masks, keeping distance, and washing hands), providing assistance to farmer groups, and easy to find or contact. Meanwhile, the performance that is considered by farmers to have the highest level of satisfaction is carrying out assistance to farmer groups, carrying out plotting demonstrations or demonstrations, and the ability of extension workers to use the local language. The results of the CSI analysis on the performance of the instructor were 74.44 percent. This value is in the range between 50 to 75 percent. This figure shows that farmers are satisfied with the performance or role performed by the agricultural extension workers.